INOVASI GAMIFIKASI WEBSITE PERSY PERFUME SEBAGAI PENGALAMAN KONSUMEN DALAM PEMILIHAN PARFUM KEPRIBADIAN SECARA DIGITAL - Pradika, Mohammad Fawaid; Alamiyah, Syifa Syarifah (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
This research will discuss how the gamification innovation of the Persy Perfume website in providing a consumer experience for digital personality perfume selection. The trend of using perfume products in Indonesia is increasing, marked by the emergence of many local perfume brands with globally competitive quality. However, product innovation is needed to increase consumer interest in using the product, one of the strategies that can be used is to provide a consumer experience in purchasing products. Persy Perfume is a local brand that uses the aroma of Indonesian spices as a unique selling product and elevates the local culture of wayang as a variant of each scent. Persy through its website provides a consumer experience through